Chronic inflammatory demyelinating polyneurophaty: assessment of the cognitive function and quality of life - Larissa Kozow; Camila Pupe; Osvaldo J. M. Nascimento (Arquivos de Neuro-Psiquiatria)
Background Studies were carried out with the objective of evaluating the quality of life (QoL) of patients affected by chronic inflammatory demyelinating polyradiculopathy (CIDP). However, the cognitive issue is still little addressed. Objectives To assess the QoL and cognitive impairment of patients with CIDP and to analyze whether there is a correlation between these parameters. Methods Seven patients with CIDP and seven paired controls were subjected to: mini-mental state examination (MMSE); Montreal cognitive assessment (MoCA); digit symbol replacement/symbol copy test (DSST); fatigue severity scale (FSS); Beck depressive inventory-I (BDI-I), and a short-form of health survey (SF-36). Results The mean age of the participants was 50 years (71.4% male). The MMSE and MoCA had no statistical difference between the groups. Patients showed superior results in the memory domain in the MoCA (5 vs. 2, p = 0.013). In the DSST, we observed a tendency for patients to be slower. There was a strong negative correlation between fatigue levels and vitality domain (SF-36). There was no significant correlation between depression levels and QoL, and there was no correlation between depression and the results obtained in the cognitive tests. The patients presented higher levels of depression (15.28 vs. 3.42, p < 0.001). A total of 57% had severe fatigue, 28.8% self-reported pain, and 57.1% complained of cramps. Conclusion There was no cognitive impairment in these patients. However, there was a tendency of slower processing speed. To better evaluate the alterations found, a study with a larger number of individuals would be necessary. Chronic inflammatory demyelinating polyradiculopathy affects the QoL of patients in different ways.